The Impact of Trust in Technological Innovation, Financial Literacy, and Social Influence Factors on Motivation in M-Banking - Yenny - Kornitasari (Universitas Islam Kadiri, 2023)
The rapid development of technology has resulted in various facilities for humans to be able to carry out various kinds of activities. One of the technological innovations from the banking sector is the presence of m-banking services. The purpose of this study was to find out and examine how the influence of technology trust, financial literacy and social influence on customer interest in using m-banking. The data collection method uses a questionnaire conducted to bank customers throughout Indonesia via Google Form. The data is processed using Principal Component Analysis (PCA) in order to obtain a new, simpler variabel. The data analysis method used in testing the hypothesis in this research is multiple linear regression analysis technique. The results show that technology trust has a significant effect on interest in using m-banking, as evidenced by the value of Sig. 0.000 <0.05, which means the higher the technology trust, the higher the interest in using m-banking. The results showed that the financial literacy variabel had a significant effect on interest in using m-baking, as evidenced by the value of Sig. 0.000 <0.05, which means the higher the financial literacy, the higher the interest in using m-banking. The results showed that the social influence variabel had a significant effect on interest in using m-baking, as evidenced by the value of Sig. 0.009 < 0.05 which means the higher the social influence received, the higher the interest in using m-banking.